2017
DOI: 10.4238/gmr16039837
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Comparison Between Real-Time Polymerase Chain Reaction and DNA-Microarray in Detection and Identification of Mycobacterium Species

Abstract: Low-cost and low-density (LCD) DNA arrays offer an easy way to detect resistance as minimal laboratory instrumentation is needed. Nucleic acid-based amplification tests allow the rapid detection of Mycobacterium tuberculosis. Recently, a real-time PCR assay for M. tuberculosis complex was introduced. Real-Time PCR and DNAmicroarray techniques were compared with the classical methods of Ziehl-Neelsen (ZN) staining and culturing. Regarding to the standard culture method, 80 positive individuals were identified o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…M. kansasii is the most common NTM detected among 3 immunocompromised patients (10%) and among the NTM (3/7 = 42.9%) in this study. Similarly, a previous study from Egypt reported M. kansasii (37.5%) as the most prevalent NTM [17]. M. kansasii was also previously reported in other countries such as Iran and Turkey as the third most common SGM in clinical isolates in the Middle East region [23].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…M. kansasii is the most common NTM detected among 3 immunocompromised patients (10%) and among the NTM (3/7 = 42.9%) in this study. Similarly, a previous study from Egypt reported M. kansasii (37.5%) as the most prevalent NTM [17]. M. kansasii was also previously reported in other countries such as Iran and Turkey as the third most common SGM in clinical isolates in the Middle East region [23].…”
Section: Discussionsupporting
confidence: 73%
“…In this study, this species was detected in an immunocompromised patient with bone marrow failure. Also, it was previously reported in Egypt [17]. Although it is rare and less virulent than other NTM, a recent study describes M. gordonae in a series of 7 immunocompetent and immunocompromised patients [28].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is based on two polymerase chain reactions which are combined prior to hybridization into one array. Identifying non-tuberculous Mycobacterium depends on Primer mix A, which is directed against highly conserved motifs flanking the internal transcribed spacer region (ITS) of the 16SrRNA gene, whereas M. tuberculosis is identified by primer mix B, which is directed against the insertion element IS6110 [ 20 ]. All procedures were performed following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In POC diagnosis, widely used urinalysis devices include dip strips or sticks for pregnancy testing, urinary tract infections (UTIs), and urine test strips for other types of analytes of urine samples, for example, Specific Gravity, Creatinine, Glucose, Ions, Ketones, Lactate, Nitrite, pH, Protein, and Uric Acid (Kingston et al 2003;Suresh et al 2018). For high throughput detection, DNA microarrays can be used for simultaneous detection of different DNA markers in urine (Gaber et al 2017). To avoid the inconvenience with urine sample storage and transportation, POC diagnosis devices, which can be easily implemented at the clinic or even at home, are highly desired in urine testing.…”
Section: Introductionmentioning
confidence: 99%